Low pressure discharge initiated by microwave radiation with stochastically jumping phase - Karas’, V.I.; Artamoshkin, A.М.; Alisov, А.F.; Bolotov, О.V.; Golota, V.I.; Karas’, I.V.; Yegorov, А.М.; Zagrebelny, I.А.; Potapenko, I.F. (Вопросы атомной науки и техники, 2012)
Present results continue the line of the previous research. In this paper the conditions of a microwave discharge ignition, its stable maintenance in air by MWRSJP, and the pressure range at which required power is minimal are found. We experimentally examine also optical characteristics of the discharge plasma in a wide range of air pressure. In general the research aims to develop a new type of sources of optical radiation. Настоящие результаты продолжают линию предыдущих исследований. В этой статье найдены условия поджига и стабильного поддержания МВИСПФ микроволнового разряда в воздухе и диапазон давлений, в котором требуемая мощность минимальна. Мы экспериментально изучили также оптические характеристики плазмы разряда в широком диапазоне давлений воздуха. В общем цель исследований − развить новый тип источников оптического излучения. Наведені результати продовжують лінію попередніх досліджень. В цій статті знайдені умови підпалу та стабільного підтримання МХВССФ мікрохвильового розряду в повітрі та діапазон тисків, у якому потрібна потужність мінімальна. Ми експериментально вивчили також оптичні характеристики плазми розряду в широкому діапазоні тиску повітря. Взагалі мета − дослідити новий тип джерел оптичного випромінювання.